ANALISIS KELAYAKAN PENGEMBANGAN INDUSTRI MEBEL MAHA KARYA DI KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR - Jumaita '; Jahrizal '; Deny Setiawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This thesis discusses the Furniture Industry Development Feasibility Analysis of Supreme Naidoo districts Kampar District Kampar Kiri. The purpose of this study was to determine the feasibility of the development of the furniture industry Masterpiece in Kampar District Kampar Kiri seen from the financial aspect. This is a descriptive quantitative research, which aims to illustrate to the reader and reveals a situation or problem, the events regarding the feasibility of the development of the furniture industry maha financial karya.Untuk using the net present value, internal rate of return, as well as the net benefit cost ratio. The results showed that the industry Furniture Masterpiece seen from the calculation of NPV calculation result is 339 847 120> o the business viable. BCR calculation results which scored 1.15> 1, then the effort feasible. IRR calculation result is 69.04% while the specified IRR is 65%, then the IRR calculation results> IRR specified, means an investment deserves. Based on the aspect of NPV, BCR and IRR accepted then the business is feasible to run.Keywords: NPV, B / C ratio, and IRR